Village in the snow Supplementary Reading Material - Hunt, Roderick (China Oxford University Press, 2012)
In Village in the Snow, the magic key takes Biff, Chip, Kipper, and Floppy to a snowy mountain village. There, they meet a boy named Lee, who is worried about a friend stuck in deep snow. The children help Lee rescue his friend using a sledge and take him back to the village. Grateful for their kindness, the villagers invite them into a warm home. Soon after, the magic key glows again, bringing them back to their own world.
This story blends adventure with acts of kindness, promoting themes of teamwork, helping others, and courage in unfamiliar places. The snowy setting also enriches vocabulary and provides opportunities for seasonal discussion and description.